Molecular Aspects of an Emerging Poplar Canker Caused by Lonsdalea populi - Li, Aining; He, Wei (Frontiers in Microbiology, 2019)
The gram-negative bacterium Lonsdalea populi causes a lethal disease known as bark canker on Populus × euramericana in China and Europe. Typical symptoms of bark canker include an abundant white-colored fluid which oozes from the infected tissues. The availability of the genomic sequence of the bacterium provided the necessary resource to launch genome-scale investigations into the mechanisms fundamental to pathogenesis. Functional analyses of a diverse group of genes encoding virulence factors and components of signaling pathways indicate that successful bark infection depends on speciﬁc responses by the pathogen to various stresses, including oxidative stress. Although physiology of resistance is well studied, the molecular processes underlying defense responses and the genetic basis of resistance to L. populi and in other poplar species remain largely unknown. Control of the disease has relied on chemical measures. Due to the genetic amenability of Lonsdalea and poplar, this pathosystem will become an important model system to unravel molecular mechanisms of bacterial pathogenicity on woody plants. Increased understanding of pathogenesis and signaling in the interaction will facilitate the management of this kind of poplar canker.